OPTIMALISASI INTEGRASI NILAI KARAKTER RELIGIUS: STUDI MULTI KASUS TENTANG UPAYA KOLABORATIF ANTARA PENGURUS PRAMUKA, GURU, DAN PIHAK SEKOLAH - Hayyu Erinda; Hakkun Elmunsyah; Hayyu Erinda (Universitas Negeri Malang, 2024)
This study investigates collaborative efforts among Scout leaders, teachers, and school authorities in integrating religious values through Scouting activities at SDIT Al-Mumtaz and SD Al-Azhar 21 Pontianak. Using a multi-case study approach, the research examines the collaboration dynamics and its impact on religious character integration. Findings reveal strong collaboration in both schools, emphasizing teacher involvement, program design, and administrative support. Scouting activities, integrated intracurricularly, effectively promote religious values, highlighting the vital role of collaboration in holistic education.